Bench-Scale Membrane Reactor for Methylcyclohexane Dehydrogenation Using Silica Membrane Module - Masahiro Seshimo; Hiromi Urai; Kazuaki Sasa; Hitoshi Nishino; Yuichiro Yamaguchi; Ryoichi Nishida; Shin-ichi Nakao (Membranes, 2021)
Methylcyclohexane-toluene system is one of the most promising methods for hydrogen transport/storage. The methylcyclohexane dehydrogenation can be exceeded by the equilibrium conversion using membrane reactor. However, the modularization of the membrane reactor and manufacturing longer silica membranes than 100 mm are little developed. Herein, we have developed silica membrane with practical length by a counter-diffusion chemical vapor deposition method, and membrane reactor module bundled multiple silica membranes. The developed 500 mm-length silica membrane had high hydrogen permselective performance (H2 permeance > 1 × 10−6 mol m−2 s−1 Pa−1, H2/SF6 selectivity > 10,000). In addition, we successfully demonstrated effective methylcyclohexane dehydrogenation using a flange-type membrane reactor module, which was installed with 6 silica membranes. The results indicated that conversion of methylcyclohexane was around 85% at 573 K, whereas the equilibrium conversion was 42%.